2019
DOI: 10.1111/jvp.12818
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the inflammatory response to two intra‐articular hyaluronic acid formulations in normal equine joints

Abstract: Intra‐articular (IA) hyaluronic acid (HA) is commonly used to treat equine arthritis. Inflammatory response or “joint flare” is a recognized potential side effect. However, the incidence and severity of inflammation following IA HA injection in horses is not well documented. This study compared the effects of two IA HA formulations of different molecular weight (MW) and a saline control on clinical signs and synovial fluid markers of inflammation in normal equine joints. Eight adult horses each had three healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 52 publications
2
14
2
Order By: Relevance
“…Neither SLS nor force‐plate analysis indicated an increase in lameness in any study horse on any observation day postinjection. Studies investigating various joint injection formulations have had variable results ranging from no change to substantial lameness 16,17,23–27 . Due to the variation in reported incidence of lameness after IA injection, it should be recognized that, although none of the 8 study horses displayed an increase in lameness following ELAA injection, this may be a possible side effect.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Neither SLS nor force‐plate analysis indicated an increase in lameness in any study horse on any observation day postinjection. Studies investigating various joint injection formulations have had variable results ranging from no change to substantial lameness 16,17,23–27 . Due to the variation in reported incidence of lameness after IA injection, it should be recognized that, although none of the 8 study horses displayed an increase in lameness following ELAA injection, this may be a possible side effect.…”
Section: Discussionmentioning
confidence: 98%
“…Horses displaying an acute reactive synovitis (joint flare), generally characterized by clinical signs of lameness ranging from mild to severe within 24‐48 h of an IA injection with any preparation, is a recognized side effect by equine practitioners and researchers 16,1716,17 . It is noteworthy that the treatment is decellularized; some studies have reported that acellular preparations of mesenchymal stem cell (MSC) content are less likely to induce an adverse immunologic event than cell‐containing counterparts 18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it cannot be concluded from the data presented here that intra‐articular administration of SYN321 induces lameness. It has been shown previously that joints injected with HA can develop significant mild‐to‐moderate inflammatory responses, often associated with lameness and joint effusion, compared with saline control joints (Johnston et al, 2020). This is consistent with our findings of swelling and potential lameness by subjective and objective lameness measures of the control limb.…”
Section: Discussionmentioning
confidence: 99%
“…Similar responses have been reported after the injection of (sterile) lipopolysaccharide (LPS) and, also, to a lesser extent, as a transient reaction to the injection of saline. They are likely a more general response of some individuals to the arthrocentesis itself and the injection of (any) material into the joint [ 32 , 52 , 53 , 54 ]. For HA, this inflammatory response can be quite severe and was, in this case, still detectable after 6 weeks, as shown by the mild increase in synovial grading score.…”
Section: Discussionmentioning
confidence: 99%